Mitochondrial ROS Triggers KIN Pathogenesis in FAN1-Deficient Kidneys - Merlin Airik; Haley Arbore; Elizabeth Childs; Amy B. Huynh; Yu Leng Phua; Chi Wei Chen; Katherine Aird; Sivakama Bharathi; Bob Zhang; Peter Conlon; Stanislav Kmoch; Kendrah Kidd; et al. (MDPI AG, 2023)
Karyomegalic interstitial nephritis (KIN) is a genetic adult-onset chronic kidney disease (CKD) characterized by genomic instability and mitotic abnormalities in the tubular epithelial cells. KIN is caused by recessive mutations in the FAN1 DNA repair enzyme. However, the endogenous source of DNA damage in FAN1/KIN kidneys has not been identified. Here we show, using FAN1-deficient human renal tubular epithelial cells (hRTECs) and FAN1-null mice as a model of KIN, that FAN1 kidney pathophysiology is triggered by hypersensitivity to endogenous reactive oxygen species (ROS), which cause chronic oxidative and double-strand DNA damage in the kidney tubular epithelial cells, accompanied by an intrinsic failure to repair DNA damage. Furthermore, persistent oxidative stress in FAN1-deficient RTECs and FAN1 kidneys caused mitochondrial deficiencies in oxidative phosphorylation and fatty acid oxidation. The administration of subclinical, low-dose cisplatin increased oxidative stress and aggravated mitochondrial dysfunction in FAN1-deficient kidneys, thereby exacerbating KIN pathophysiology. In contrast, treatment of FAN1 mice with a mitochondria-targeted ROS scavenger, JP4-039, attenuated oxidative stress and accumulation of DNA damage, mitigated tubular injury, and preserved kidney function in cisplatin-treated FAN1-null mice, demonstrating that endogenous oxygen stress is an important source of DNA damage in FAN1-deficient kidneys and a driver of KIN pathogenesis. Our findings indicate that therapeutic modulation of kidney oxidative stress may be a promising avenue to mitigate FAN1/KIN kidney pathophysiology and disease progression in patients.